2018
DOI: 10.1038/s41467-018-04737-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome resequencing reveals world-wide ancestry and adaptive introgression events of domesticated cattle in East Asia

Abstract: Cattle domestication and the complex histories of East Asian cattle breeds warrant further investigation. Through analysing the genomes of 49 modern breeds and eight East Asian ancient samples, worldwide cattle are consistently classified into five continental groups based on Y-chromosome haplotypes and autosomal variants. We find that East Asian cattle populations are mainly composed of three distinct ancestries, including an earlier East Asian taurine ancestry that reached China at least ~3.9 kya, a later in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
322
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(412 citation statements)
references
References 57 publications
54
322
3
2
Order By: Relevance
“…And such phylogeographic differentiation pattern also was observed in sheep (Zhao, Yu, Zhang, Kong, & Zhao, 2013), horse (Yue et al, 2012) and pig (Huo et al, 2016). It had been known that several species (cattle, goats, sheep and pig) showed a multiple domestication pattern in different regions (Beja-Pereira et al, 2006;Chen et al, 2018;Larson et al, 2005;Luikart et al, 2001;Pedrosa et al, 2005). Phylogenetic analysis reveals abundant genetic diversity and several haplogroups.…”
Section: Discussionmentioning
confidence: 69%
“…And such phylogeographic differentiation pattern also was observed in sheep (Zhao, Yu, Zhang, Kong, & Zhao, 2013), horse (Yue et al, 2012) and pig (Huo et al, 2016). It had been known that several species (cattle, goats, sheep and pig) showed a multiple domestication pattern in different regions (Beja-Pereira et al, 2006;Chen et al, 2018;Larson et al, 2005;Luikart et al, 2001;Pedrosa et al, 2005). Phylogenetic analysis reveals abundant genetic diversity and several haplogroups.…”
Section: Discussionmentioning
confidence: 69%
“…; Chen et al . a, b). In addition, to improve economic performance, exotic commercial breeds have been introduced into southern China since the 1970s to upgrade native breeds (Qiu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Considering that several of the breeds analyzed in this study were also used by Chen et al . (), we infer that Y2‐102/104‐158 and Y2‐106/108/110/112‐158 belong to sub‐haplogroups Y2a and Y2b respectively. A previous study showed that Y2‐90‐158 was the most frequent haplotype in African N'Dama taurine cattle (Edwards et al .…”
Section: Y‐chromosome Haplotypes and Diversity (H±sd) Of 34 Chinese Cmentioning
confidence: 78%
“…In a recent whole‐genome resequencing study, Chen et al . () identified two distinct sub‐haplogroups in each of the Y2 (Y2a/b) and Y3 (Y3a/b) haplogroups.…”
Section: Y‐chromosome Haplotypes and Diversity (H±sd) Of 34 Chinese Cmentioning
confidence: 99%
See 1 more Smart Citation